Daniel Dennett and the computational turn - Dorbolo, J.; Barnette, R.; Bynum, T.; Cavalier, R.; Moor, J.; Rosenthal, D.M.; Uzgalis, B. (Minds and Machines, 2006)
Keywords: dept.phi

Flourishing ethics - Bynum, Terrell Ward (Ethics and Information Technology, 2006)
This essay describes a new ethical theory that has begun to coalesce from the works of several scholars in the international computer ethics community. I call the new theory Flourishing Ethics because of its Aristotelian roots, though it also includes ideas suggestive of Taoism and Buddhism. In spite of its roots in ancient ethical theories, Flourishing Ethics is informed and grounded by recent scientific insights into the nature of living things, human nature and the fundamental nature of the universe-ideas from today's information theory, astrophysics and genetics. Flourishing Ethics can be divided conveniently into two parts. The first part, which I call Human-Centered FE, is focused exclusively upon human beings - their actions, values and characters. The second part, which I call General FE, applies to every physical entity in the universe, including humans. Rather than replacing traditional great ethical theories, Flourishing Ethics is likely to deepen and broaden our understanding of them. © Springer Science+Business Media B.V. 2006.
Keywords: Aristotelian ethics; Astrophysics; Computer ethics; Cybernetics; Cyborg ethics; Entropy; Good and evil; Information ethics; Infosphere; Just consequentialism; Philosophical aspects; Robot ethics; dept.phi

Introduction: genocide's aftermath - Card, Claudia; Marsoobian, Armen T (Metaphilosophy, 2006)
Keywords: dept.phi

Dynamic traditions: why globalization does not mean homogenization - Volkman, Richard (Journal of Information, Communication and Ethics in Society, 2006)
In light of the relation between culture and markets, an analysis of cultural evolution reveals that globalization will not lead to the homogenization of world cultures. © 2006, Emerald Group Publishing Limited
Keywords: Culture; Globalization; Market; Tradition; dept.phi; peer-reviewed